Guidelines for library services to prisoners - 3rd Edition - Güler Demir (Türk Kütüphaneciliği)
Prison library is one of the most important components of rehabilitation of incarcerated persons. This paper is the translation of the latest revision guidelines issued by IFLA, titled “Guidelines for Library Services to Prisoners” (by Vibeke Lehmann and Joanne Locke) These 2005 guidelines, developed to assist prison library management and staff in providing the prisoners with efficient and satisfying library and information service, are flexible to be adapted to local conditions and settings.